Persepsi Mahasiswa PGMI terhadap Inovasi Pembelajaran Berbasis Karya Seni: Tinjauan Atribut Difusi Inovasi - Asep Ediana Latip; Prita Farihatunnisa; Bintang Maharani Meha; Alya Khoerunnisa (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the perceptions of students in the Madrasah Ibtidaiyah Teacher Education Program (PGMI) toward art-based learning innovation from the perspective of the Diffusion of Innovation Theory using a quantitative survey approach. The participants were PGMI students who had experienced art-based learning, and data were collected through a closed-ended questionnaire distributed via Google Form, developed based on five innovation diffusion attributes: relative advantage, compatibility, complexity, trialability, and observability, as well as the level of innovation acceptance. The data were analyzed using descriptive statistics to identify trends in students’ perceptions for each attribute. The results indicate that all diffusion of innovation attributes achieved mean scores in the high to very high categories, with observability and acceptance of innovation showing the highest values. These findings suggest that the benefits of art-based learning are clearly observable and highly accepted by students. In addition, art-based learning is perceived to have greater relative advantages than conventional learning, strong compatibility with the PGMI educational context, and a relatively low level of complexity. Overall, the findings demonstrate that art-based learning is perceived as effective, relevant, and easy to adopt within the context of madrasah teacher education. This study implies that art-based learning has strong potential as an innovative instructional strategy to support creativity development, student engagement, and the professional readiness of PGMI students as prospective teachers. Future research is recommended to involve a broader range of respondents and to examine the long-term impact of art-based learning implementation on teaching practices in schools.